ANALISIS FINANSIAL DAN STRATEGI PENGEMBANGAN USAHA PERDAGANGAN TELUR ECERAN: STUDI KASUS DI PASAR TRADISIONAL KOTA BANDAR LAMPUNG - Tri Yunita Sari; Agus Hudoyo; Adia Nugraha (Lampung University, 2015)
Since the beginning of 2000’s, the modern markets, supermarkets and minimarkets, have been growing rapidly in Bandar Lampung. They have been being the competitors for the traditional markets that sell agricultural commodities, such as egg. The question is whether they are profitable and whether the egg retailers in the traditional markets can compete with the modern markets in Bandar Lampung. This study tries to answer these questions by using the financial and the SWOT analyses. All 44 egg retailers in the traditional markets, Bandar Lampung are the respondents in this study. Based on the financial analysis the rate of return of the egg retail business is 8.74% per month. The result of SWOT analysis showed that the egg retail trade businesses in traditional market at quadrant I. This case showed that egg retail trade in traditional market were profitable and located on the growing areas. The top strategy utilized the long enough experience trading to build relationships with suppliers and that supply of fulfilled will continue available. Key words: egg, rate of return, retail trade, SWOT analysis